Pengaruh Pelatihan Kewirausahaan dan Motivasi Berwirausaha terhadap Niat Berwirausaha bagi Penyandang Disabilitas di Yayasan Teman Hebat Berkarya Jakarta - Dewi, Repita; Nandang, Nandang; Ismail Yusup (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research is motivated by the limited employment opportunities for people with disabilities, making entrepreneurship training and entrepreneurial motivation crucial factors in increasing entrepreneurial intentions. The purpose of this study was to determine the perceptions of entrepreneurship training, entrepreneurial motivation, and entrepreneurial intentions, and to determine whether there is an influence between entrepreneurship training and entrepreneurial motivation on entrepreneurial intentions among people with disabilities at the Yayasan Teman Hebat Berkarya in Jakarta. The research method used was quantitative with a descriptive and verification approach. Based on the results of classical assumption tests and hypothesis testing, entrepreneurship training and entrepreneurial motivation had a positive effect on entrepreneurial intentions among people with disabilities at, amounting to 74.4%, while the remaining 25.6% was influenced by other variables not discussed in this study. The inconsistency of the training curriculum with the participants' actual needs, as well as low expectations and motivation for entrepreneurship, resulted in people with disabilities being less prepared to start businesses, resulting in underutilization of the skills acquired from the training.